Hydrogen-rich syngas production from bi-reforming of greenhouse gases over zirconia modified Ni/MgO catalyst - Farooqi A.S.; Yusuf M.; Zabidi N.A.M.; Saidur R.; Shahid M.U.; Ayodele B.V.; Abdullah B. (John Wiley and Sons Ltd, 2023)
Amorphous carbon; Carbon dioxide; Catalyst supports; Greenhouse gases; Hydrogenation; Magnesia; Nickel compounds; Physicochemical properties; Zirconia; Bi-reforming of methane; CH 4; Co-precipitation; Greenhouses gas; Methane reaction; Ni/MgO catalyst; Performance; Reforming of methane; Syngas production; ]+ catalyst; Coprecipitation